ANALISIS PENERAPAN TAX PLANNING DALAM UPAYA MEMINIMALKAN PPN TERHUTANG PADA CV. MIKITA COOKIES - Dwiyatmoko Pujiwidodo (Universitas Bina Sarana Informatika, 2017)
To implement the savings tax obligations and the tax burden, the company can implement tax planning. Tax planning is legal or process attempts to manipulate, organize business and the transaction so that the tax payer is a tax debt in an amount of at least but still within the scope of the provisions of the taxation laws in force. This study aims to identify and analyze the impact of tax planning in an effort to minimize the value-added tax payable on CV. Mikita Cookies. Based document of VAT in 2014, CV. Mikita Cookies transact with suppliers who have registered themselves as PKP or not PKP, so that not all purchases issuing tax invoices, it affects the calculation of VAT. Of the various ways of tax planning VAT, in this study, the authors apply the optimization of crediting of input tax. From the discussion, it can be seen that the document in 2014, VAT owed to be paid is Rp. 212 046 749, -, with total purchases of PKP Rp. 10,917,702,280 and the total purchase Non PKP Rp. 810 189 115, After the VAT tax planning with patterns of maximizing tax creditable input VAT payable then the resulting total of Rp. 131 027 838, -. Assumed in 2014 that CV. Mikita Cookies only deal with PKP, so that on every purchase of goods / services CV. Mikita Cookies get a tax invoice